2018
DOI: 10.1002/aenm.201803072
|View full text |Cite
|
Sign up to set email alerts
|

High Thermoelectric Performance in Polycrystalline SnSe Via Dual‐Doping with Ag/Na and Nanostructuring With Ag8SnSe6

Abstract: Single crystalline SnSe is one of the most intriguing new thermoelectric materials but the thermoelectric performance of polycrystalline SnSe seems to lag significantly compared to that of a single crystal. Here an effective strategy for enhancing the thermoelectric performance of p‐type polycrystalline SnSe by Ag/Na dual‐doping and Ag8SnSe6 (STSe) nanoprecipitates is reported. The Ag/Na dual‐doping leads to a two orders of magnitude increase in carrier concentration and a convergence of valence bands (VBM1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
102
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 57 publications
4
102
0
Order By: Relevance
“…Since the PFs were limited at a higher temperature, such a peak ZT was not very competitive compared with those inrevious reports. 19,20,36,44 However, compared with the results of normal LPS or HD methods, a higher averaged ZT value (ZT ave ) was achieved using the LPHD technique as summarized in Fig. 6b.…”
Section: Thermal Conductivity and Zt Valuementioning
confidence: 86%
See 1 more Smart Citation
“…Since the PFs were limited at a higher temperature, such a peak ZT was not very competitive compared with those inrevious reports. 19,20,36,44 However, compared with the results of normal LPS or HD methods, a higher averaged ZT value (ZT ave ) was achieved using the LPHD technique as summarized in Fig. 6b.…”
Section: Thermal Conductivity and Zt Valuementioning
confidence: 86%
“…The excellent TE performance could be realized by increasing the power factor (PF = a 2 s) or compressing the thermal conductivity as much as possible. [6][7][8] Usually, several strategies such as resonant doping, 9,10 band convergence [11][12][13] and carrier concentration optimization 14,15 can effectively increase the power factor, while the lattice thermal conductivity k l can be reduced by the all-scale hierarchical structuring [16][17][18][19] and dense defects [20][21][22][23] as phonon scattering centers.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high cost of synthesizing SnSe single crystal and its poor mechanical properties impede the practical applications of this material. Therefore, many studies have been carried out for studying the thermoelectric performance of 3D polycrystalline SnSe [3][4][5][6][7][8][9] and 2D SnSe 10 . It has been found that the ZT value of polycrystalline SnSe is dramatically reduced as compared to that of single-crystal SnSe because of the existence of grain boundaries (GBs) in polycrystalline structures, which can reduce the electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the performance, chemical doping has been used. Previous studies have shown that alkali elements [3][4][5] , halogens 6,7 , and Ag 8,9 are the promising dopants for increasing the ZT value of 3D polycrystalline SnSe. For instance, the ZT value of K-doped polycrystalline SnSe is 1.1 at 773 K 5 , which is more than twice the original value of pure polycrystalline SnSe (0.5) at 823 K 12 , but still much less than that (2.6-2.8) of its single crystal counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of nano-size precipitate significantly depresses the lattice thermal conductivity. As a result, an enhanced ZT of ~1.3 is obtained [3].…”
mentioning
confidence: 97%